Gender and Communication: Analyzing Tweet Length, Sentiment, and Lexical Patterns on X (Twitter) - Romadloni, Annisa; Sari, Laura (Journal of English Language and Education, 2025)
This study explores gendered communication patterns on X by examining tweet length, sentiment expression, and lexical choices in 20.050 tweets across 26 variables. Through sentiment analysis using the Bing Lexicon and word frequency analysis, the research investigates how male and female users differ in their digital communication styles. The study also incorporates non-parametric statistical tests, such as the Mann-Whitney U and Wilcoxon rank sum tests, to assess significant differences in tweet length and sentiment scores between genders. Results show that women tend to write shorter, more positive tweets, often reflecting a more personal and relational communication style. In contrast, men’s tweets are generally longer, incorporating more action-oriented language and a broader range of topics. While sentiment analysis revealed a trend of more positive tweets from women, the lack of statistical significance in sentiment differences highlights the complex nature of gendered expression in digital spaces. This research contributes to the understanding of gendered communication on social media and suggests the need for future studies to examine the intersectionality of gender with other social factors.